Swot Analysis of Village Food Safety Cadres in The Safe Food Village Program in Gorontalo, Indonesia - T Masaliha, Musyafar; Heryani, Wiwie; Misdar, Andriani; Ikram, Yuniarty (National Journal of Community Medicine, 2024)
Village Food Safety Cadres must possess a high level of proficiency in the field of food safety. The purpose of this study was to assess the efficacy of Village Food Safety Cadres in the Safe Food Village Program in Gorontalo, with the aim of promoting the engagement of these cadres. This was done to facilitate the formulation of recommendations aimed at optimizing the performance of cadres in future endeavors. This study uses qualitative descriptive methods. The study findings indicate that there are multiple barriers to establishing active village food safety cadres in Gorontalo. These obstacles include a lack of experience, skills, and knowledge among local food safety cadres, as well as their own self-concept. Additionally, the appointment of cadres is not voluntary but rather done by the Village Head, which hinders the formation of a strong self-concept as a cadre. Furthermore, socio-cultural characteristics, particularly language issues, pose challenges as some cadres are highly proficient in local languages, making it difficult to comprehend materials in Indonesian. The communities that needed to be supported were composed of individuals with varied educational backgrounds, thus requiring the adaptation of counselling methods to cater to their specific needs. To effectively train and meet the necessary qualifications of active cadres, it is essential to create media platforms for spreading food safety information that incorporate local knowledge. This can be achieved by utilizing local languages that cater to the different demographic characteristics of the communities being nurtured. Furthermore, it is imperative to make dedicated endeavors to enhance the knowledge of cadres on food safety, thereby fostering a positive self-perception.